Associated factors for the decrease of force of inspiratory muscle in pregnant women of high risk - Pereira, Alianny Raphaely Rodrigues; Souza, Helga Cecilia Muniz de; Duarte, Adryelle Fernandes; Nascimento, Camila Maria Mendes; Maia, Juliana Netto; Reinaux, Cyda Maria Albuquerque (ABCS Health Sciences, 2024)
Introduction: The gestational period brings anatomical and physiological changes to women in several systems, especially the respiratory system. Objective: To determine whether there is an association between gestational age (GA), Diabetes, uterine fundal height (UFH), Body Mass Index (BMI), level of dyspnea, and physical activity with maximum respiratory and nasal pressures. Methods: Cross-sectional study that included 55 high-risk pregnant women in the 2nd and 3rd trimester of pregnancy at the Obstetrics Outpatient Clinic of the Hospital das Clínicas in Recife – PE, Brazil, personal, sociodemographic, anthropometric, clinical and Maximal Inspiratory Pressure (MIP) data were described and nasal inspiratory pressure (NIP), that, using regression and multivariate analysis, analyzed the influence of risk factors for high-risk pregnancy with NIP considering a p<0.005. Results: Among the pregnant women, according to the clinical variables, it was observed that 56.4% (n=31) had a gestational age above 28 weeks, 27.3% (n=15) diabetes, 25.5% (n=14) asthma, 43.6% (n=24) Gestational Hypertension, 56.4% (n=31) obesity, 85.5% (n=47) complaints of dyspnea 38.1% (n=21) mild to severe dyspnea and 65.5% (n=36) vigorous physical activity. Low MIP (76.76 cmH2O) and NIP (68.62 cmH2O) values were found for age. An association was observed between an increase in UFH and a decrease of 0.8 cmH2O in NIP, regardless of gestational age. Conclusion: High-risk pregnant women in the second and third trimester of pregnancy have decreased NIP and MIP with a negative association of UFH with NIP regardless of gestational age.